Programs on sexual education in Panama - Vergès, Claude (Acta Bioethica, 2007)
Which place occupies pleasure in sexual education programs? In Panama, as in other Latin American countries, violence against children and women does not allow people to realize own bodylines and less their right to pleasure. Present programs about sexual education, pregnancy prevention and AIDS promote the use of preservatives and abstinence but do not include the ethics of pleasure. Frequently, the health and training personnel are not prepared to speak about the topic. The use of sexual pleasure as a merchandise in media creates greater confusion. Bioethics must integrate psychological and anthropological studies and a sense of humanity to allow this personnel to work with persons towards the integral appropriation of human beings.